2008
DOI: 10.1007/s10557-008-6101-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Insulin to Improve Glycemic Control in Diabetes Mellitus

Abstract: These findings are of great interest as it is possible that the prevention of macrovascular complications in type 2 diabetes may require the use of those glucose lowering drugs which have additional anti-inflammatory effects in addition to the control of comorbid conditions (hypertension and dyslipidemia) associated with this disease. Results of future clinical trials are awaited to confirm the benefits of this approach in the primary and secondary prevention of macrovascular complications in type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 121 publications
(126 reference statements)
1
5
0
Order By: Relevance
“…Hypoglycemic effects of metformin correlated to a higher insulin release. Some studies indicate that insulin may exert an anti-inflammatory response, independent of its effects on glycemia by mechanisms of NO release, and inhibition of NFκB signaling thus decreasing ICAM-1 and MCP-1 expression (Dandona et al, 2008;Sun et al, 2014). Our study showed pro-hyperglycemic effects by BTE as indicated by increased levels of fasted and fed glucose as well as lesser glucose tolerance, whereas levels of insulin were not changed significantly.…”
Section: Discussionsupporting
confidence: 45%
“…Hypoglycemic effects of metformin correlated to a higher insulin release. Some studies indicate that insulin may exert an anti-inflammatory response, independent of its effects on glycemia by mechanisms of NO release, and inhibition of NFκB signaling thus decreasing ICAM-1 and MCP-1 expression (Dandona et al, 2008;Sun et al, 2014). Our study showed pro-hyperglycemic effects by BTE as indicated by increased levels of fasted and fed glucose as well as lesser glucose tolerance, whereas levels of insulin were not changed significantly.…”
Section: Discussionsupporting
confidence: 45%
“…Studies using surrogate clinical measures of atherosclerosis showed that pioglitazone significantly slowed progression of carotid intima–media thickness and prevented progression of coronary atherosclerosis vs glimepiride [79, 80]. Insulin may exert anti-inflammatory actions that could be anti-atherogenic/cardioprotective, although this remains controversial [81]. Insulin may also lower LDL-cholesterol and triacylglycerol levels [82, 83].…”
Section: Other Important Pathophysiological and Clinical Effectsmentioning
confidence: 99%
“…Diabetes induces oxidative and inflammatory stress, vasoconstrictor responses, thrombotic phenomena and pro-apoptotic effects on endothelial cells (22).…”
Section: Discussionmentioning
confidence: 99%